Pengaruh Edukasi Gizi dengan Media Video Animasi tentang Gizi Seimbang di SMA 4 PSKD JAKARTA - Dampang, Damelya Patricksia; Patricia Divany (Seminar Nasional Penelitian dan Abdimas, 2024)
Adolescence is a period of transition from child to adult, during which changes occur rapidly in physical, cognitive and emotional growth and development. Providing education in the form of videos is one approach to convey information and messages that are easy to understand. Showing videos can stimulate the senses of hearing and vision, making adolescents more quickly receive information and remember it. This study was conducted to determine the effect of giving animated videos on eating habits, physical activity, and knowledge about balanced nutrition before and after being given nutrition education. This study used a Quasi-Experimental design with a Pretest-Posttest with Control Group Design approach. The research was conducted in June 2023 with a total of 68 students at SMA 4 PSKD Jakarta. Measurement of variables using a questionnaire includes eating habits, physical activity, and nutritional knowledge. Data analysis was carried out univariate and bivariate with the Wilcoxon Test. The results showed the effect of giving animated video media on eating habits (p value = 0.000), physical activity (p value = 0.000), and knowledge about balanced nutrition (p value = 0.000). Based on this study, it is known that animated videos are effective in improving eating habits, physical activity, and nutritional knowledge in adolescents. Keywords — animation video, eating habit, nutritional knowledge, physical activity